2017
DOI: 10.4067/s0719-81322017000100045
|View full text |Cite
|
Sign up to set email alerts
|

Testicular echotexture is not a viable method to indirectly evaluate the spermatogenic parameters in Nelore bulls

Abstract: ABSTRACT. The objective of this study was to evaluate the testicular echotexture of Nelore bulls and to correlate it with spermatogenic parameters. Forty one bulls aged 3-5 years, with body weight of 510.2 ± 21.61 kg were selected for the study. The animals were subjected to ultrasonography, using a portable device coupled with a linear transducer at a frequency of 7.5 MHz. Immediately afterwards they were castrated and the testicular tissue was treated with Karnovsky fixative. Next, the fragments were embedde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…(2015), since the tunica albuginea echogenicity does not change. We conclude that this method has advantages compared to the simple measurement of pixel intensity performed by other researchers (Dias et al., 2017; Oliveira Pinho et al., 2013; Tomlinson et al., 2017).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…(2015), since the tunica albuginea echogenicity does not change. We conclude that this method has advantages compared to the simple measurement of pixel intensity performed by other researchers (Dias et al., 2017; Oliveira Pinho et al., 2013; Tomlinson et al., 2017).…”
Section: Discussionmentioning
confidence: 54%
“…(2015) showed that mean testicular heterogeneity was positively correlated with the total spermatozoal output. However, other researchers did not find a correlation between pixel intensity and sperm production or semen quality in dogs (Dias et al., 2017; Pinho et al., 2012; Tomlinson et al., 2017). Many researchers have reported that testicular echogenicity increases during sexual development directly with seminiferous tubules growth (Camela et al., 2018; Hamm & Fobbe, 1995; Pozor et al., 2017; Silva et al., 2012).…”
Section: Discussionmentioning
confidence: 91%
“…However, in our study conditions, neither the initial LW nor immunocastration affected the pixel intensity of the testicles, although a later histological and immunohistochemical study of the testicular parenchyma revealed a decrease in the diameter of the seminiferous tubules and an abnormal cell population in VA animals (Monleón et al, ). In this sense, some authors have suggested that testicular echogenicity is not a viable method for the indirect analysis of cellular population in the seminiferous epithelium, intrinsic spermatogenic performance, or the Sertoli cell index or semen quality (Dias et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…[Correction added on 20 November 2019, after first online publication: 'Monleón et al, in press' has been updated to 'Monleón et al, 2020'. ] In this sense, some authors have suggested that testicular echogenicity is not a viable method for the indirect analysis of cellular population in the seminiferous epithelium, intrinsic spermatogenic performance, or the Sertoli cell index or semen quality (Dias et al, 2017).…”
Section: Testicular Traitsmentioning
confidence: 99%